Rapid modification of neutron star surface magnetic field: a proposed mechanism for explaining radio emission state changes in pulsars. Issue 4 (22nd April 2021) - Geppert, U; Basu, R; Mitra, D; Melikidze, G I; Szkudlarek, M
ABSTRACT: The radio emission in many pulsars shows sudden changes, usually within a period, that cannot be related to the steady state processes within the inner acceleration region (IAR) above the polar cap. These changes are often quasi-periodic in nature, where regular transitions between two or more stable emission states are seen. The durations of these states show a wide variety ranging from several seconds to hours at a time. There are strong, small-scale magnetic field structures and huge temperature gradients present at the polar cap surface. We have considered several processes that can cause temporal modifications of the local magnetic field structure and strength at the surface of the polar cap. Using different magnetic field strengths and scales, and also assuming realistic scales of the temperature gradients, the evolutionary time-scales of different phenomena affecting the surface magnetic field were estimated. We find that the Hall drift results in faster changes in comparison to both Ohmic decay and thermoelectric effects. A mechanism based on the partially screened gap (PSG) model of the IAR has been proposed, where the Hall and thermoelectric oscillations perturb the polar cap magnetic field to alter the sparking process in the PSG. This is likely to affect the observed radio emission resulting in the observed state changes.